Research in parental involvement : methods and strategies for education and psychology - Latunde, Yvette C. (Palgrave Macmillan, 2017)
"This book examines the process of conducting research on parental involvement in an effort to promote academic achievement across all school levels, income levels, and racial lines, theories, and research. Latunde explores the policies that have emerged to support the role of families and home-school collaboration in the education of youth, and evidence supporting home school collaboration and the need for parental involvement to improve student outcomes. She defines parental research and its role in our understanding of parental involvement and student outcomes and examines federal and state mandates for parental involvement and shares specific parental involvement resources. The nuances in parental involvement are critical to understanding the roles family play in the academic achievement youth, and how schools may partner with parents for success."--Resumé vydavatele
Keywords: pedagogický výzkum -- metodologie; rodina a škola; educational research -- methodology; home and school; příručky; handbooks and manuals